How middle school special and general educators make sense of and respond to changes in teacher evaluation policy - Braun, Alisha M. B.; Youngs, Peter (Education Policy Analysis Archives, 2020)
In this multiple case study, we apply sensemaking theory to examine and compare how middle school special and general educators perceive and respond to teacher evaluation reform, including formal classroom observations, informal walkthroughs, and student growth measures. Our findings reveal that special educators experience conflict between the policy’s main elements and their understandings of how to effectively teach students with disabilities. Furthermore, special and general educators held contrasting beliefs regarding the appropriateness of evaluation. Our findings illustrate the importance of acknowledging differences in special and general educators’ roles and responsibilities and encourage policymakers to reconsider uniform teacher evaluation policies.